A deeper look at the relationship between dispositional mindfulness and empathy: Meditation experience as a moderator and dereification processes as mediators. (15th October 2020) - Fuochi, Giulia; Voci, Alberto
Abstract: Studies on the relationship between dispositional mindfulness and empathy reported results that vary across specific components of the constructs and employed measures. We investigated the associations between facets of mindfulness (acting with awareness, nonjudging, nonreactivity, describing, observing) and dimensions of empathy (perspective taking, empathic concern, personal distress), while considering meditation experience of respondents as a moderator (Study 1), and variables associated to the mindfulness-related dereification process (adaptive emotion regulation, decentering, reduced rumination, nonattachment, and social connectedness) as mediators (Studies 2 and 3). We hypothesized that most facets of mindfulness would be positively associated with perspective taking and empathic concern, and negatively with personal distress (H1), that the association between mindfulness facets and empathy would be stronger in meditators (H2), and that the relationship between mindfulness and empathy would be mediated by adaptive emotion regulation (H3) and by the other mindfulness-related dereification constructs (H4). Results substantially supported H1, H2, and H3, and H4 for what concerned decentering, nonattachment, and social connectedness; unexpectedly, rumination conveyed a negative indirect effect from mindfulness facets – except observing – to empathy. Findings clarify the ambivalent (positive via adaptive emotion regulation and dereification, negative via rumination) relationship between mindfulness and empathy, and the moderating role of meditation.